Penerapan Metode Praktek dalam Pembiasaan Sholat Pada Mata Pelajaran Fiqih - Nurhadi, Nurhadi (LIPI, 2016)
Prayer is a pillar of religion, one part of the pillars of Islam. Good and bad human status in the world or in akherat sourced from good and bad prayer. Therefore learning habituation to worship worship should be inculcated early on. One indicator of the lack of prayer habituation especially in the third grade students in SDI Science and Tahfizh Imam Syafi'i Tulungagun today is less active students in following the learning activities. This is coupled with the fact that the learning process applied still apply the old paradigm. Namely lectures, frequently asked questions and assignments. To enable students in the learning process, the use of practice method is very appropriate, because this method can encourage cooperation and activeness of students to improve the obligatory prayers 5 times. The implementation process itself includes: (1) Planning (planning), (2) Implementing action (acting), (3) Observation (observing) and (4) Reflection (reflection).